Simulation Experiment of TSR Promotes Cracking of Coal Generation H2S - Qigen Deng; Yinsheng Du; Yanjie Yang; Fajun Zhao (Geofluids)
Thermochemical sulfate reduction (TSR) is one of the main contributors to the formation of hydrogen sulfide (H2S) in coal seam strata. Four reaction systems (coal, coal+water, coal+water and MgSO4, and coal+water and MgSO4 and AlCl3) were selected and simulated from 250°C to 600°C with eight temperature steps using a high-temperature and high-pressure reaction device, and the evolution characteristics of the gaseous products of hydrocarbons (methane, C2-5) and nonhydrocarbon gases (CO2, H2, and H2S) were studied. Thermal simulation experiments showed that the TSR led to the reduction of heavy hydrocarbons, and the presence of salts accelerated the evolution of hydrocarbons; SO42-, Al3+, and Mg2+ had a certain promoting effect on the TSR, which increased the total amount of alkane gas, H2S, and CO2 production. Improving the salinity of the reaction system can promote the occurrence of TSR, and water plays a key role in hydrocarbon generation evolution and the TSR.